Genesis and Development of A âNonpartisanâ Political Actor: The Formation of the Jamaâah Islah Malaysia (JIM) and its Roots in Western Europe - Lemiere, Sophie (Al-Jamiah: Journal of Islamic Studies, 2009)
This paper looks at the genesis and development of the Jamaâah Islah Malaysia (JIM), a modernist-reformist Islamist organisation that today has played a vital and visible role in the political landscape of Malaysian politics. Little is known about the early genesis of JIM, and how it began in the 1970s and 1980s as a student-based cadre organisation, created by Malaysian Muslim students studying abroad in Europe and North America. JIMâs roots therefore lie in the Islamic Representative Council (IRC) that was a semi-underground student-cadre movement that was created outside Malaysia, and which aimed to bring about the Islamisation of Malaysian society through the process of social and political mobilisation. Working through the archives of JIM today and interviewing the foundermembers of JIM and the IRC, this paper is the first historical account of the formation and development of IRC and JIM to be published.